Differential expression of snoRNAs in oral squamous cell carcinomas: new potential diagnostic markers - Cintia Chamorro-Petronacci; Mario Perez-Sayáns; Maria Elena Padín-Iruegas; Xabier Marichalar-Mendia; Mercedes Gallas-Torreira; Abel García García (Taylor & Francis Group, 2018)
Background: Small nucleolar RNAs (snoRNAs) are small non-coding RNA sequences whose most studied function is ribosome biogenesis. The altered expression of snoRNA is observed in tumoral processes such as breast cancer and multiple myeloma. However, we have not found any references to snoRNAs in oral squamous cell carcinomas (OSCC) in the literature at the time this article was written. Material and methods: We have analyzed snoRNA expression in frozen OSCC tissue samples and have compared them to healthy controls. RNA was extracted from a total of eight OSCC samples and eight control samples, measuring the differential expression of small RNAs with the Affymetrix® miRNA 4.1 Array Plate microarray platform. Results: Results were analyzed using the Transcriptome Analysis Console 3.0 (TAC) software. We obtained a total of 16 deregulated snoRNAs of which one was over expressed and 15 were under expressed. SnoRNAs expression was altered in OSCC and could serve as a diagnostic marker.